Monitoring and evaluation framework for hypertension programs. A collaboration between the Pan American Health Organization and World Hypertension League - Campbell, Norm R. C. (J Clin Hypertens (Greenwich), 2018)
The Pan American Health Organization (PAHO)–World Hypertension League (WHL) Hypertension Monitoring and Evaluation Framework is summarized. Standardized indicators are provided for monitoring and evaluating national or subnational hypertension control programs. Five core indicators from the World Health Organization hearts initiative and a single PAHO‐WHL core indicator are recommended to be used in all hypertension control programs. In addition, hypertension control programs are encouraged to select from 14 optional qualitative and 33 quantitative indicators to facilitate progress towards enhanced hypertension control. The intention is for hypertension programs to select quantitative indicators based on the current surveillance mechanisms that are available and what is feasible and to use the framework process indicators as a guide to program management. Programs may wish to increase or refine the number of indicators they use over time. With adaption the indicators can also be implemented at a community or clinic level. The standardized indicators are being pilot tested in Cuba, Colombia, Chile, and Barbados.